1972
DOI: 10.1002/bjs.1800590802
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the floor of the anterior cranial fossa. The selection of patients for dural repair

Abstract: 1. A series of 87 patients operated on because of subfrontal fractures is reported. In 73 of these a fistulous lesion (connecting the brain with the nose or the accessory air sinuses) was displayed and was repaired. Almost always a bifrontal exploration has been made, because the lesions were bifrontal in 43 per cent of cases. The mean follow‐up period was 4 years; to date no instances of postoperative meningitis or rhinorrhoea have occurred. 2. Our experience suggests that cerebrospinal rhinorrhoea accompanyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…5,7 Our experience agrees with this finding and those of many other reports that have demonstrated that compound skull base fractures can indeed be complicated by meningitis, regardless of their association with a CSF leak. 2,5,9,[12][13][14][15]21,22,26,28…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,7 Our experience agrees with this finding and those of many other reports that have demonstrated that compound skull base fractures can indeed be complicated by meningitis, regardless of their association with a CSF leak. 2,5,9,[12][13][14][15]21,22,26,28…”
Section: Discussionmentioning
confidence: 99%
“…Instead, surgical decision making is primarily guided by whether the fracture is associated with persistent cerebrospinal fluid (CSF) rhinorrhea. 1,4,25 Rhinorrhea or tension pneumocele, however, can develop many (5-45) years after injury, 8,9,13,14,16,19,21,22 and a fatal attack of pneumococcal meningitis, without preced-ing CSF rhinorrhea, may be the first presentation of a posttraumatic fistula. 8 The reasons for poor healing in such cases are not fully understood.…”
mentioning
confidence: 99%
“…While some advocate early surgical treatment [11,15], others prefer delayed surgery [14,16,18]. At this centre surgery is usually performed at the end of the second week after the trauma, when brain edema has mostly resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Post-traumatic CSF leakage is a common complication in head injury patients, since pneumo-cephalus and cerebral contusion of base of frontal lobes strongly suggest dural laceration (Jefferson et al, 1972;Ghoshhajra, 1980). Traditionally, CSF rhinorrhea has been treated conservatively, and surgical treatment remains a matter of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…The modern keyhole craniotomy concept was proposed by Fukushima (Fukushima et al, 1991;Jefferson et al, 1972), who noted the possibility of reducing traumatic manipulation of all tissue encountered, with the concept that the skin incision, craniotomy, or dural opening need not approximate the size of a keyhole. We applied this concept to treat traumatic optic neuropathy and cerebrospinal fluid (CSF) leakage.…”
Section: Introductionmentioning
confidence: 99%